: : : / The penal system, crime theory, punishment theory (2023)
.
The book deals with the Saudi penal system in its general section, and includes the theory of crime with its elements and conditions, the theory of punishment and types of penalties and measures, with a comparison with other criminal legislations.
.
.
Keywords: Criminal law -- Saudi Arabia; Crime -- Definition; Punishment -- Saudi Arabia; Saudi Arabia -- Criminal provisions; Print books